The medieval filmscape : reflections of fear and desire in a cinematic mirror - Woods, William F., 1942- (McFarland & Company, Inc., Publishers, 2014)
"This book has three parts: the introduction enters the medieval film world, describing its typical features and showing how they create a convincing sense of its time; three short chapters discuss authenticity, simplicity and spectacle--the roots of film medievalism; and six longer chapters comment on individual films. The author describes what goes into a medieval film"--